Empowering Rural Women through Transformative Leadership: Insights from KWT Pawon Gendis - Kertamukti, Rama; Anderson, Shaun M; Asy'ari, Asrul Zain (Jurnal Ilmiah Peuradeun, 2025)
This research focuses on women's empowerment in rural communities, specifically in the context of transformational leadership applied by Dwi Martuti Rahayu in KWT Pawon Gendis, a farm women's group in Salakmalang Village. The issue raised is how transformational leadership can be adapted and applied in a more local social context, with the aim of exploring the dimensions of transformational leadership that are effective in empowering women in the village. This research used a qualitative approach with a case study method, with data collected through in-depth interviews, participatory observation, and documentation analysis. This research showed that Dwi Martuti Rahayu successfully applied four main dimensions of transformational leadership-Idealized Influence, Inspirational Motivation, Individualized Consideration, and Intellectual Stimulation, which were instrumental in increasing women's capacity and participation in social and economic activities, visualised in the dynamics of her activities. The discussion shows that while transformational leadership theory is generally applied in the context of formal organizations, its application in rural communities has proven effective, with the important caveat that it must be tailored to local needs and challenges. The research make a significant contribution to the development of transformational leadership-based empowerment models in rural contexts and potentially pave the way for further research in this area.